The fairy tale fixers. Case file #1, Cinderella - Underwood, Deborah (The fairy tale fixers, 2025)
The Investigators meet The First Cat in Space in this hilarious graphic novel. Fairy and Mouse will forever change young readers' perspectives on stepmothers, princes, and pumpkins as they help Cinderella set things right when her carriage veers off course. Every fairy tale needs a fairy. Because sometimes stories go off the rails, and this fairy knows just what to do to fix them. Actually, he doesn't . . . He makes it up as he goes along. And sometimes he needs help. A lot of help. Which is where Mouse comes in. Together, she and Fairy will make sure this tale has a happily ever after--just maybe not the one you expect.